2005
DOI: 10.1063/1.2120892
|View full text |Cite
|
Sign up to set email alerts
|

Textured Ca3Co4O9 thermoelectric oxides by thermoforging process

Abstract: Using thermoforging process, dense Ca3Co4O9 (Co349) thermoelectric oxides have been successfully textured. The various parameters influencing the formation of the Co349-textured material have been investigated. The electrical transport measurements show an anisotropy of the resistivity in good agreement with scanning electron microscopy observations. Texture is quantified by neutron-diffraction measurements and correlated to anisotropic resistivity measurements and Seebeck coefficients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
54
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 14 publications
8
54
2
Order By: Relevance
“…The maximum of the distribution near 4.9 m.r.d. on the {001} pole figure for both samples is comparable to the average orientations observed so far in Co349 ceramics [18,19,21,35]. The minimum of density is nearly 0, indicating that no other orientation component is present in the samples.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The maximum of the distribution near 4.9 m.r.d. on the {001} pole figure for both samples is comparable to the average orientations observed so far in Co349 ceramics [18,19,21,35]. The minimum of density is nearly 0, indicating that no other orientation component is present in the samples.…”
Section: Resultssupporting
confidence: 83%
“…However one cannot exclude a priori an effect of its larger crystallite distribution, as seen in the broader centre of its {001} pole figure compared to SPS-1123K. The positive Seebeck coefficient S value is an indication [3,11,21] of the hole mediated conduction in Ca 3 Co 4 O 9 .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Owing to this fact, a large amount of research has been carried out on improving the TE properties of randomly oriented polycrystalline Ca 3 Co 4 O 9 ceramics, but with very limited improvement. [2][3][4][5] Therefore, several efforts have been made to improve the texture of Ca 3 Co 4 O 9 ceramic by various methods, such as spark plasma sintering, 6 magnetic alignment, 7 and hot-forging processes, 8 owing to a general belief that the grain boundaries negatively affect the electrical conductivity and hence the TE properties of this system. The epitaxial growth and c-axis-oriented films fabricated using the pulsed laser deposition (PLD), 9,10 radio-frequency magnetron sputtering, 11 and the topotactic ion exchange method 12 have proven to be successful in improving the TE properties of this system.…”
Section: Introductionmentioning
confidence: 99%
“…3a) gives evidence that to increase the electrical conductivity and the power factor an improvement of the connectivity and orientation of the grains is required. One of the possible approaches to reduce the porosity of the sintered materials and align the grains is the hot-forging, and in general it was shown that the performance of piezoelectric [14], ferroelectric [15] and thermoelectric [16] oxide ceramics is greatly enhanced by the hot-forging technique. Another possible approach to obtain aligned grains was widely applied to superconducting ceramics and it is called "melt textured growth" (MTG) [17].…”
Section: P-type Oxides: Cualomentioning
confidence: 99%